Pro-inflammatory NK-like T cells are expanded in the blood and inflamed intestine in Crohn's disease - Chiarolla, Cristina M.; Schulz, Axel R.; Meir, Michael; Ferrara, Sebastian; Xiao, Yin; Reu-Hofer, Simone; Romero-Olmedo, Addi J.; Falcone, Valeria; Hoffmann, Katja; Büttner-Herold, Maike; Prelog, Martina; Rosenwald, Andreas; et al. (Mucosal Immunology, 2024)
Altered intestinal immune homeostasis leads to chronic inflammation in Crohn's disease (CD). To address disease- and tissue-specific alterations, we performed a T cell-centric mass cytometry analysis of peripheral and intestinal lymphocytes from patients with CD and healthy donors’ PBMCs. Chronic intestinal inflammation enforced activation, exhaustion, and terminal differentiation of CD4+ and CD8+ T cells and a relative enrichment of CD4+ regulatory T (Treg) cells. Moreover, enigmatic rare Treg subsets appeared upon inflammation, e.g. CD4+FOXP3+HLA-DR+TIGIT– and CD4+FOXP3+CD56+, expressing pro-inflammatory IFN-γ upon in vitro stimulation. Some conventional T (Tcon) cells acquired NK-like features. In CD patients’ blood, not well studied CD16+CCR6+CD127+ T cells appeared, being CD4+ or CD8+, a phenotype inducible on healthy T cells by CD blood plasma. Upon CD16-mediated antibody binding, they could attain effector function. These findings suggest an uncommon pro-inflammatory innate-like differentiation of Treg and Tcon cells with acquisition of non-specific cytotoxicity. Most likely, this is both cause and consequence of intestinal inflammation during CD.
CRIS-Team Scopus Importer:2025-02-04
Keywords: CD16; CD56; Crohn's Disease; CyTOF; TIGIT